2018
DOI: 10.1039/c7me00131b
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the molecular weight distribution from atom transfer radical polymerization using deep reinforcement learning

Abstract: We devise a novel technique to control the shape of polymer molecular weight distributions (MWDs) in atom transfer radical polymerization (ATRP). This technique makes use of recent advances in both simulation-based, modelfree reinforcement learning (RL) and the numerical simulation of ATRP. A simulation of ATRP is built that allows an RL controller to add chemical reagents throughout the course of the reaction. The RL controller incorporates fully-connected and convolutional neural network architectures and ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 135 publications
(139 reference statements)
0
38
0
Order By: Relevance
“…While much of the work so far has focused on deep generative modeling for drug molecules, 24 there are many other application domains which are benefiting from the application of deep learning to lead generation and screening, such as organic light emitting diodes, 25 organic solar cells, 26 energetic materials, 10,27 electrochromic devices, 28 polymers, 29 polypeptides, [30][31][32] and metal organic frameworks. 33,34 Our review touches on four major issues we have observed in the field.…”
mentioning
confidence: 99%
“…While much of the work so far has focused on deep generative modeling for drug molecules, 24 there are many other application domains which are benefiting from the application of deep learning to lead generation and screening, such as organic light emitting diodes, 25 organic solar cells, 26 energetic materials, 10,27 electrochromic devices, 28 polymers, 29 polypeptides, [30][31][32] and metal organic frameworks. 33,34 Our review touches on four major issues we have observed in the field.…”
mentioning
confidence: 99%
“…In Chemistry domains, researchers have had access to multidimensional data of unprecedented scale and accuracy, that characterize the systems/processes to be modeled. A collection of different examples of optimization based on ML approaches can be found in Kowalik et al (2012) Specifically, ML contributions have involved a variety of systems including drugs (Griffen et al, 2018), polymers (Li et al, 2018a), polypeptides (Grisoni et al, 2018;Müller et al, 2018), energetic materials (Elton et al, 2018), metal organic frameworks (He et al, 2018;Jørgensen et al, 2018a;Shen et al, 2018), and organic solar cells (Jørgensen et al, 2018a).…”
Section: Machine Learning For Optimization: Challenges and Opportunitiesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] MWD of produced polymer usually depends on the polymerization mechanism and kinetics. [11][12][13][14][15][16][17][18][19][20] In general, living anionic polymerization produces chains with narrow MWD, while traditional free radical polymerization yields broadly distributed chains. [20] To better understand the connection between kinetics and MWD as well as to clarify which theory is correct or more proper, many efforts have been made to simulate MWD.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Three methods, i.e., moments, Monte Carlo, and solving ordinary differential equations directly, have been developed. [14,16] Among them, the most used is the method of moments because it is not only based on clear reaction mechanism and kinetic equation, but also ratio (RR) of chain propagation to chain transfer can give an impact on the degree of uniformity of chain length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation